Numerical study on the atomization performance of aviation biofuel with high blending ratio - Yanyu Cui; Changhong Xiong; Shugang Yang; Qingmiao Ding; Kai Zhang; Chen Xu (PLoS ONE, 2025)
Blending aviation biofuel with conventional jet fuel helps reduce carbon emissions in aviation. However, high blending ratios (≥50%) can impact engine atomization performance. This study uses a three-dimensional simulation of gas-liquid flow in a centrifugal nozzle with the volume of fluid (VOF) method to evaluate the atomization performance of aviation biofuels with traditional jet fuel at different blending ratios (0%, 40%, 60%, 80%, 100%), under varying temperatures and nozzle inlet pressures. The simulation results align well with empirical data, showing deviations of less than 10%. As the inlet pressure increases from 0.2 MPa to 1.0 MPa, the nozzle outlet velocity increases by 127.0%, and the liquid film thickness decreases by 41.8%, improving atomization performance. At 0.2 MPa, higher blending ratios (≥50%) leads to thicker liquid films, reducing atomization efficiency. However, at 1.0 MPa, the effect of blending ratio on atomization becomes less significant, with the difference in liquid film thickness reduced to 4.2%. Fuel temperature significantly affects atomization, with more noticeable differences between low- and high-blending fuels. As temperature rises from 0°C to 50°C, liquid film thickness decreases, with a reduction of 14.6% for low-blending fuel and 52.8% for high-blending fuel.